EFFECTS OF DRYING METHODS ON THE LOW-TEMPERATURE REACTIVITY OF VICTORIAN BROWN COAL TO OXYGEN - (:unkn) unknown (BUTTERWORTH-HEINEMANN LTD, 1992)
The effects of air drying and thermal dewatering on the low temperature oxygen reactivity of Victorian brown coal have been investigated in the temperature range 35-55-degrees-C and at 100 kPa oxygen pressure using coal samples ground to < 100 mesh. An attempt has also been made to relate the low temperature oxygen reactivity of the coal to its free radical concentration as measured prior to oxidation. Two rate models, the Schmidt and Winmill models, have been adapted to include the initial free radical concentration of the coal samples as the drying method sensitivity parameter in lieu of the concentration of oxygen-reactive sites in the coal material. The experimental results show that air drying, which reduces the free radical concentration of the coal, causes a decline in its oxygen reactivity whereas thermal dewatering, which causes an increase in the free radical concentration of the coal, enhances its oxygen reactivity. Air drying does not affect the distribution of the consumed oxygen in the oxidation products. A difference is observed in the case of the thermally dewatered coal samples, The correlation of the two rate models adopted is considered equally satisfactory. However, only the values obtained for the two activation energies in the Winmill model reflect the changes caused by thermal dewatering in the oxidation pattern of the coal. The activation energy values obtained from the two models are within the range of those quoted in the literature for the abstraction of hydrogen from various arene structures by free radicals.
Keywords: BROWN COAL; REACTIVITY; OXYGEN; OXIDATION